An Arabic language framework for semantic web - Beseiso M.; Ahmad A.R.; Ismail R. (2023)
This research study was basically aimed at addressing the current lack of Arabic support within majority of semantic web tools technologies and applications. It will also address the on-going problem of the lack of resources for Arabic research or semantic web technologies that support the Arabic text. While there may have already been various researches in the past that have been conducted in order to develop ontology-based and optimized semantic framework with the English content, there were very few researches that were developed for the Arabic language. This paper, reports on the survey of the support for the Arabic language in some of the existing semantic web technologies and gives future scenario in applying Semantic Web for Arabic applications. Finally, we propose a new framework intended to add a semantic web layer to the current web based application in order to improve the process of linking, integrating, and searching for different types of applications. The proposed framework will serve Arabic language processing, although it is designed to be adapted to any other languages. 2011 IEEE.